Core-shell structured carbon nanotube-poly(methylmethacrylate) beads as thermo-conductive filler in epoxy composites. (June 2018) - Vu, Minh Canh; Bae, Young Han; Yu, Min Ji; Islam, Md. Akhtarul; Kim, Sung-Ryong
Abstract: A facile and novel method has been developed for the preparation of highly thermo-conductive epoxy-based composites. The core-shell structure is formed with 'functionalized carbon nanotubes (sCNTs)' as shell encapsulated on the plasma-treated poly(methylmethacrylate) (pPMMA) as core. Effective thermo-conductive pathways are realized through core-shell structured bead-bead conduction throughout the composites. The core and shell have been characterized by Fourier transform infrared analysis and zeta potential measurement. The core-shell arrangement has visualized by scanning electron microscopy, which supported the expectation that the shell being positively charged would be assembled on the negatively charged core forming a highly conductive outer surface of the non-conductive core. The thermal conductivity of the epoxy composites increased from 0.19 W m −1  K −1 of neat epoxy to 0.96 W m −1  K −1 at 1 wt% of sCNTs in sCNT@pPMMA beads. The method developed in this work introduces a new approach of using non-conductive polymer beads as constituting element in conductive framework formation.